PENENTUAN KELAYAKAN ASPEK FINANSIAL USAHA FUTSAL X DI KOTA BATAM - Asmarawati, Citra Indah; Sidabutar, Joel Alexander; Sadiq Ardo Wibowo (LPPM-ITEBA, 2024)
One promising business opportunity is the futsal field business, in line with the increasing popularity of this sport in Indonesia. However, before deciding to open a futsal field business, it is important to analyze the financial feasibility of the business first. Financial feasibility analysis is the process of assessing and evaluating the financial aspects of an investment or business plan to determine whether the investment is feasible or not from a financial perspective. This analysis is very important for evaluating the financial prospects of a business plan before deciding to implement it. Analysis of the feasibility of the planet futsal field business from a financial aspect shows that this business is feasible to run by meeting the criteria of the various assessment methods used. The results of the Net Present Value (NPV) analysis are positive at IDR 38,812,042, the Internal Rate of Return (IRR) is 7% which is greater than the required rate of return, the Payback Period is 9 months, and the multi-product Break Even Point (BEP) is shows the minimum number of rental hours that must be met per operational hour so that the business does not experience losses.